Multipler Effect in East Java (Input-Output Analysis Approach) - Fahrizal Taufiqqurrachman (JEJAK: Jurnal Ekonomi dan Kebijakan, 2022)
This study aims to examine the fundamentals of the economy of East Java with an Interregional Input-Output analysis approach. Produce 5 leading sectors (BL 1 FL 1) namely manufacturing industry, electricity supply, gas, transportation and warehousing, information and communication and company services. Changes in final demand (Household consumption, LNPRT consumption, Government Consumption, Gross Fixed Capital Formation, Inventory Change, Overseas Exports, Exports Between Provinces) indicate that the processing industry is very dominant in experiencing changes. The multiplier impact 1) output is dominated by electricity, gas 2) income is dominated by the Defense Administration and Mandatory Social Security 3) Employment is dominated by agriculture, forestry and fisheries. The Impact of Spread including manufacture, procurement of electricity, gas, construction, transportation and warehousing, provision of accommodation and food and drink, information and communication, company services, health services, and social activities. The Degree of Sensitivity including agriculture, forestry and fisheries, manufacture, procurement of electricity, gas, wholesale and retail trade, car and motorcycle repair, transportation and warehousing, information and communication, company services.